Divergences in Leaf Economic Traits Among Five Congeneric Tree Species in a Subtropical Forest - Qiuju Chen; Linyan Wu; Rong Li; Zhi Yin; Yinping Jiang; Yanjiao Mao; Chao Zhang; Yi Jin; Xiaoxin Tang; Yin Yi (Ecology and Evolution, 2025)
ABSTRACT Exploring the differences in leaf economic traits between co‐occurring congeneric angiosperm species will advance the understandings of coexistence mechanisms of closely related species in sympatry. Here, we investigated the divergence in eight leaf economic traits and the underlying ecological drivers among 293 individual plants of five congeneric tree species of Carpinus (Betulaceae) that commonly co‐occur in a karst forest in southwestern China. We found there was generally a large proportion of trait variation that resided at the interspecific level, and these congeneric species commonly differed in leaf economic traits. We also found these congeneric species frequently exhibited divergent topographic habitat‐mediated trait shifts and displayed trait ranking reversals along the environmental gradients. However, these congeners did not differ in plant size‐dependent shifts of leaf economic traits. These findings imply the separation in resource‐use strategies among the congeneric species of Carpinus, which might contribute to resource niche partitioning and hence facilitate their coexistence in the karst forests.